2020
DOI: 10.3389/fmed.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcitriol on the Renal Microvasculature Differentiation Disturbances Induced by AT1 Blockade During Nephrogenesis in Rats

Abstract: Alterations in the renal vasculature during fetal programming can cause disturbances in renal structure and function that persist into adulthood. Calcitriol can affect cellular differentiation and proliferation, and promote endothelial cell maintenance, each of which is a key event in nephrogenesis. Calcitriol is a negative endocrine regulator of the renin gene. Rats exposed to renin-angiotensin system (RAS) antagonists during lactation have been shown to develop renal disorders, which demonstrated that the RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In a previous study, rats treated with losartan during lactation showed alterations in renal function and structure, including hydronephrosis, papillary atrophy, endothelial dysfunction and aberrant endothelial structure, that were mitigated by the treatment with calcitriol. 45 Similarly, Soares et al . 46 among patients with end-stage renal failure, showed that the combination treatment of RASI with cholecalciferol could prevent the decline in glomerular filtration in the randomized VITAL Study paricalcitol was able to reduce albuminuria and blood pressure in patients with diabetic nephropathy who were already on RAS inhibitor therapy.…”
Section: Vitamin D and Renin–angiotensin System Inhibitorsmentioning
confidence: 93%
“…In a previous study, rats treated with losartan during lactation showed alterations in renal function and structure, including hydronephrosis, papillary atrophy, endothelial dysfunction and aberrant endothelial structure, that were mitigated by the treatment with calcitriol. 45 Similarly, Soares et al . 46 among patients with end-stage renal failure, showed that the combination treatment of RASI with cholecalciferol could prevent the decline in glomerular filtration in the randomized VITAL Study paricalcitol was able to reduce albuminuria and blood pressure in patients with diabetic nephropathy who were already on RAS inhibitor therapy.…”
Section: Vitamin D and Renin–angiotensin System Inhibitorsmentioning
confidence: 93%
“…The lack of Ang II/AT 1 axis during nephrogenesis leads to post‐natal renal morphological alterations in rodents with genetic deletion of RAS components (Hilgers et al, 1997; Ishida et al, 1998; Pentz et al, 2004; Sequeira‐Lopez & Gomez, 2021; Takahashi et al, 2005) or treated with RAS blockers after birth (Deluque et al, 2020; Madsen et al, 2010). At birth the renal morphology of Agt‐KO is comparable to controls, but in the first weeks of life alterations including papillary atrophy, hydronephrosis and vascular concentric hypertrophy develop (Nagata et al, 1996; Niimura et al, 1995; Tsuchida et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Paricalcitol (6 ng/day, Zemplar ® , Abbvie Laboratories, North Chicago, IL, USA) and vehicle (0.9% NaCl solution) were administered through a mini osmotic pump (Model 2004, Alzet, Cupertino, CA, USA) implanted in the back of the animal. This dose was selected according to the previously described [27]. Paricalcitol treatment started two days before adriamycin (ADR) administration and continued throughout the observation for 27 days, allowed by the mini osmotic pump model approach.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Only the kidney tissues were deproteinized with 95% ethanol (4 • C) (1:2) and centrifuged (4000× g for 5 min) again. The supernatants of urine, plasma, and kidney tissue were subjected to an analysis of NO content using the NO/ozone technique described previously with a Sievers analyzer (Sievers 280 NOA, Frederick, CO, USA) [27]. As described in previous studies, the Bradford method was used to determine protein levels in renal tissue [27].…”
Section: No In Urine Plasma and Renal Tissue Measurementmentioning
confidence: 99%
See 1 more Smart Citation